Religion, modernity, globalisation nation-state to market - Gauthier, François 1973- (Abingdon, Oxon ; New York Routledge, 2020)
The rise and fall of the nation-state regime -- The market and the problem of social order: from Adam Smith to Keynes -- Neoliberalism and the rise of the market regime -- From consumption to consumerism -- RCT, RIP! Rethinking marketisation -- From mediatisation to hyper-mediatisation -- The marketisation of religion -- Indonesia: from ratio to market Islam -- From Pope to coach: marketed institutions, re-invented traditions -- Conclusion. Thinking a changing world.
Keywords: Globalization -- Religious aspects; Religion -- Economic aspects; Neoliberalism -- Religious aspects; Religion And Politics; Nation-state and globalization; Globalization ; Religious aspects; Religion ; Economic aspects; Neoliberalism ; Religious aspects; SOCIAL SCIENCE / Sociology of Religion; RELIGION / Religion, Politics & State; BUSINESS & ECONOMICS / Economics / Theory